Redefining Criteria to Ensure Adequate Sentinel Lymph Node Biopsy With Dual Tracer for Breast Cancer - Xu, Li; Yang, Jiqiao; Du, Zhenggui; Liang, Faqing; Xie, Yanyan; Long, Quanyi; Chen, Jie; Zeng, Helin; Lv, Qing (Frontiers in Oncology, 2020)
Background: For sentinel lymph node biopsy (SLNB) in patients with breast cancer, the dual tracer of blue dye and radioisotope with the 10% rule that all nodes with radioactive count of 10% or more of the hottest node ex vivo should be removed is widely accepted. However, the cut-off point of radioactivity is being questioned for possibly excessive removal of negative nodes. Methods: To compare different percentile rules and optimize the criteria for identifying SLNs, we established a database which prospectively collected the radioactivity, status of blue dye and the pathological results of each SLN in breast cancer patients who successfully underwent SLNB with a combination of methylene blue and radioisotope. Results: A total of 2529 SLNs from 1039 patients were identified from August 2010 to August 2019. 16.4%(414/2529) positive nodes were removed at a cost of 83.6%(2115/2529) negative nodes removed excessively. Up to 17.9%(375/2115) negative nodes were removed as radioactively hot nodes without blue staining. By gradually increasing the threshold by each 10%, the number of negative nodes identified reduced by 18.2%(385/2115) with only three node-positive patients (1.0%) missed to be identified using the “40% + blue” rule. In patients with ≥ 2 SLNs removed, 12.3%(238/1942) negative nodes avoided unnecessary removal with only 0.8%(2/239) positive patients missed with the “hottest two + blue” rule. Conclusions: Our data indicated that the “40% + blue” rule or the “hottest two + blue” rule for SLNB with the dual tracer of blue dye and radioisotope may be considered as a potential alternative rule to minimize extra nodes resected. Nonetheless, it should be validated by prospective trials with long-term follow-up.